The teacher training of the university professor. A challenge to rethink and revisit the practice of teaching in higher education - Ariana DE VINCENZI (Ediciones Universidad de Salamanca, 2012)
Since the late twentieth century, a series of social, cultural, political and economic changes have impacted university teaching. These changes have called for an in-depth review of teaching practices based on the transmission of information shifting towards a model that is focused on the training of professionals with a strong sense of social responsibility, and on the learning process of students. Reflecting upon teaching practices in the university classroom entails a long process of conceptual review and cultural restructuring. One must not ignore that some university professors may view the demands of teacher training as a didactic bureaucratization process derived from governmental policies on the improvement of educational quality. This cultural resistance is indicative of the individualism and curricular fragmentation prevailing in the practice of university teaching, and hinders a critical review of teaching practices in the light of current social needs. In this regard, the review calls for an analysis of the configuration of the professional identity of university professors, recovering their interests and needs in practicing the profession. Experience and vocation are not enough to exercise university teaching, systematic teacher training is required. This paper presents a proposal for the institutional development of teacher training of the university professor, and guidance for its implementation. The relevance of the proposal lies in the opportunity to improve the quality of education and conduct a critical review of the professional identity of university professors.